Repackaging Character Literacy and Numeracy-Oriented RADEC Learning Model Through Teacher Professional Development Program - Indra Gunawan; Wahyu Sopandi; Hany Handayani; Nurul Fatonah; Indra Suhendra; Yusup Maulana (Studies in Learning and Teaching, 2023)
A number of literature state that numeracy and literacy skills are the initial capital for every individual to be able to learn. However, it is known that teachers still experience difficulties in teaching character, literacy and numeracy to students in the learning process. This research was conducted to transfer abilities to teachers to design learning with student worksheets which integrate the Read, Answer, Discuss, Explain, and Create (RADEC) learning model. The research model used in this research is Educational Design Research (EDR) since in the research an intervention will be carried out in the form of a workshop on preparing RADEC-based learning designs at Private Elementary Labschool UPI Purwakarta while in several previous studies EDR was also conducted through interventions such as professional development activities in the form of workshop. At the workshop stage itself, numeracy indicators were explained in detail and thoroughly with guidance from the Guide to Strengthening Literacy and Numeracy in Schools. In relation to numeracy, teachers' understanding of numeracy competency is still not comprehensive but on the other hand, surprisingly the teachers were able to integrate numeracy indicators in the lesson plan of non-mathematic subject. Overall, through RADEC learning model, all teachers be able to select appropriate spoken, written, or visual texts or resources based on their individual students' needs and interests. As a result, they can make the necessary changes to the syllabus's contents; choose the best methods, approaches, and techniques to use; plan the most appropriate activities to carry out; and select, design, or adapt the teaching materials.